A new species of Habenaria (Orchidaceae, Orchideae) from Qinghai Province, China - Ma, Chong-Bo; Wang, Han-Chen; Deng, Tan; Lin, Peng-Chen; Jin, Xiao-Hua (Phytotaxa, 2023)
Habenaria qinghaiensis, a new species of Orchidaceae from Qinghai Province, is described and illustrated. Molecular phylogenetic analysis based on nuclear ITS (nrITS) and two plastid (matK and rbcL) DNA markers indicates that H. qinghaiensis belongs to H. josephi group (sect. Diphyllae s.l.). It is morphologically similar to H. josephi and H. tibetica, but differs from the former by having petals shallowly 2-lobed at base, lateral lobes of lip 1.8–2.2 cm long, lip with cushion-like appendage at entrance of spur, and from the latter by having almost glabrous bracts, petals and ovary, lip with cushion-like appendage at entrance of spur, and three stigmas.